COVID-19 and Sepsis Are Associated With Different Abnormalities in Plasma Procoagulant and Fibrinolytic Activity. Issue 1 (January 2021) - Bouck, Emma G.; Denorme, Frederik; Holle, Lori A.; Middelton, Elizabeth A.; Blair, Antoinette M.; de Laat, Bas; Schiffman, Joshua D.; Yost, Christian Con; Rondina, Matthew T.; Wolberg, Alisa S.; Campbell, Robert A.
Abstract : Objective: Coronavirus disease 2019 (COVID-19) is associated with derangement in biomarkers of coagulation and endothelial function and has been likened to the coagulopathy of sepsis. However, clinical laboratory metrics suggest key differences in these pathologies. We sought to determine whether plasma coagulation and fibrinolytic potential in patients with COVID-19 differ compared with healthy donors and critically ill patients with sepsis. Approach and Results: We performed comparative studies on plasmas from a single-center, cross-sectional observational study of 99 hospitalized patients (46 with COVID-19 and 53 with sepsis) and 18 healthy donors. We measured biomarkers of endogenous coagulation and fibrinolytic activity by immunoassays, thrombin, and plasmin generation potential by fluorescence and fibrin formation and lysis by turbidity. Compared with healthy donors, patients with COVID-19 or sepsis both had elevated fibrinogen, d-dimer, soluble TM (thrombomodulin), and plasmin-antiplasmin complexes. Patients with COVID-19 had increased thrombin generation potential despite prophylactic anticoagulation, whereas patients with sepsis did not. Plasma from patients with COVID-19 also had increased endogenous plasmin potential, whereas patients with sepsis showed delayed plasmin generation. The collective perturbations in plasma thrombin and plasmin generation permitted enhanced fibrin formation in both COVID-19 and sepsis. Unexpectedly, the lag times to thrombin, plasmin, and fibrin formation were prolonged with increased disease severity in COVID-19, suggesting a loss of coagulation-initiating mechanisms accompanies severe COVID-19. Conclusions: Both COVID-19 and sepsis are associated with endogenous activation of coagulation and fibrinolysis, but these diseases differently impact plasma procoagulant and fibrinolytic potential. Dysregulation of procoagulant and fibrinolytic pathways may uniquely contribute to the pathophysiology of COVID-19 and sepsis. Abstract : Supplemental Digital Content is available in the text.